2020
DOI: 10.3390/polym12102362
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polylactide (PLA) Stereocomplexation on the Microstructure of PLA/PBS Blends and the Cell Morphology of Their Microcellular Foams

Abstract: Polylactide foaming materials with promising biocompatibility balance the lightweight and mechanical properties well, and thus they can be desirable candidates for biological scaffolds used in tissue engineering. However, the cells are likely to coalesce and collapse during the foaming process of polylactide (PLA) due to its intrinsic low melt strength. This work introduces a unique PLA stereocomplexation into the microcellular foaming of poly (l-lactide)/poly (butylene succinate) (PLLA/PBS) based on supercrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…PLA has a longer degradation time and better stability than PLGA and is often used to produce ultra-long-lived products. PLA is widely used in sutures [ 21 ], bone implants [ 22 ], screws [ 22 ], and continuous drug delivery [ 23 , 24 , 25 ]. LUPRON DEPOT ® (4/6 months) [ 26 ], which uses PLA as a slow-release material, has been approved by the U.S. Food and Drug Administration for various diseases, including prostate cancer, endometriosis, myoma, and precocious puberty.…”
Section: Introductionmentioning
confidence: 99%
“…PLA has a longer degradation time and better stability than PLGA and is often used to produce ultra-long-lived products. PLA is widely used in sutures [ 21 ], bone implants [ 22 ], screws [ 22 ], and continuous drug delivery [ 23 , 24 , 25 ]. LUPRON DEPOT ® (4/6 months) [ 26 ], which uses PLA as a slow-release material, has been approved by the U.S. Food and Drug Administration for various diseases, including prostate cancer, endometriosis, myoma, and precocious puberty.…”
Section: Introductionmentioning
confidence: 99%
“…When choosing water bath-induced foaming, the ease of hydrolysis of PLA should be taken into account, which may impact the performance of the foamed material, although temperature-induced foaming is a relatively short process. Sun et al [ 67 ] prepared PLLA/PBS/PDLA composite foam by temperature-induced intermittent foaming. The effects of the introduction of poly(butylene succinate) (PBS) and PDLA on the crystallization behavior and cellular structure of PLLA were investigated.…”
Section: Supercritical Co 2 Foaming Technologiesmentioning
confidence: 99%
“…This process significantly reduces the induction period, leading to the formation of highly dense spherulites [ 27 ]. Given the advantageous crystallization process, researchers have observed significant improvement in the PLA barrier properties [ 28 , 29 , 30 ]. One study found that the water vapor permeability values of solution-casted stereocomplex-based films were significantly reduced (~14–23%) compared to those of the PLLA/PDLA homopolymers [ 31 ].…”
Section: Introductionmentioning
confidence: 99%